2009
DOI: 10.1186/1471-2261-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Swedish snuff and incidence of cardiovascular disease. A population-based cohort study

Abstract: BackgroundThe relationship between smoking and an increased incidence of cardiovascular diseases is well known. Whether smokeless tobacco (snuff) is related to myocardial infarction (MI) or stroke is still controversial. Aim of this study was to explore whether snuff users have an increased incidence of MI or stroke.MethodsA total of 16 754 women and 10 473 men (aged 45–73 years), without history of cardiovascular disease (CVD), belonging to the population-based "Malmö Diet and Cancer" study were examined. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 28 publications
12
58
0
Order By: Relevance
“…Cardiovascular effects of smokeless tobacco have been less studied, but there are reports on acute autonomic and hemodynamic effects such as endothelial dysfunction 5,6 and increased blood pressure, heart rate, and blood levels of adrenaline. 7,8 No increased risk of MI incidence has been observed in previous studies, [9][10][11][12][13][14][15][16] although 2 meta-analyses have reported a seemingly increased risk for fatal MI, 17,18 which suggests that snus use may predispose to arrhythmic or other serious complications of MI. Nicotine exposure has also been associated with increased vulnerability for ventricular fibrillation after MI in animal studies.…”
Section: Clinical Perspective On P 332mentioning
confidence: 77%
See 1 more Smart Citation
“…Cardiovascular effects of smokeless tobacco have been less studied, but there are reports on acute autonomic and hemodynamic effects such as endothelial dysfunction 5,6 and increased blood pressure, heart rate, and blood levels of adrenaline. 7,8 No increased risk of MI incidence has been observed in previous studies, [9][10][11][12][13][14][15][16] although 2 meta-analyses have reported a seemingly increased risk for fatal MI, 17,18 which suggests that snus use may predispose to arrhythmic or other serious complications of MI. Nicotine exposure has also been associated with increased vulnerability for ventricular fibrillation after MI in animal studies.…”
Section: Clinical Perspective On P 332mentioning
confidence: 77%
“…Apart from 1 exception based primarily on tobacco chewers, 26 no increase in risk of MI incidence has been observed. [9][10][11][12][13][14][15][16] The risk of MI mortality has been elevated in some studies, 15,27 which suggests an increased case-fatality rate, with a 13% increased risk in a 2009 meta-analysis 17 and a 28% increased risk in a 2012 pooled meta-analysis. 18 In a review and meta-analysis, smoking cessation was associated with a 36% reduction in risk of all-cause mortality among patients with coronary heart disease.…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%
“…Overall, our results do not indicate any strong associations between snus use and at least the CVD risk factors included here. This should serve as one piece in the puzzle where most prospective studies fail to find any excess risk of myocardial infarction incidence among snus users [1,[7][8][9]41,42], including a recent pooled analysis of eight prospective observational studies [43]. However, as some studies have indicated an increased risk for fatal myocardial infarction [44][45][46], stroke [46,47] and heart failure [48] for snus users, the need for further studies on snus and health remains.…”
Section: Discussionmentioning
confidence: 98%
“…This negative association may be attributed to reduced caloric intake due to a central effect of smoking, impaired smell or taste, a change in food preference, or a direct metabolic effect on the absorption or storage of calories, or an increase in energy expenditure [48]. The association between smokeless tobacco use and increased risk of cardiometabolic-related morbidities and mortalities has been well characterized [4951]. However, in our study, smokeless tobacco use was associated with a lower BMI in women.…”
Section: Discussionmentioning
confidence: 99%